2017
DOI: 10.1111/anu.12607
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized effect of citric acid and phytase supplementation on growth performance and nutrient digestibility of Labeo rohita

Abstract: A 2-month trial was conducted to record the effect of citric acid and phytase supplementation on growth performance and nutrient digestibility in labeo rohita. Nine treatment (T) diets having 0, 500 and 1,000 FTU/KG phytase and 0, 15 and 30 g/kg citric acid were prepared and were designated as T1, T2, T3, T4, T5, T6, T7, T8 and T9 diets.There were three replicates for each of the test diets. Fish samples (n = 324) were stocked in different tanks and were fed with T1, T2, T3, T4, T5, T6, T7, T8 and T9 diets. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
(41 reference statements)
7
8
0
Order By: Relevance
“…The result revealed that fish fed D5 had the highest a significant different (p < 0.05) on growth performance and feed utilization in comparison to the control and diets of interaction phytase and citric acid. This is in agreement with other studies on different species including L. rohita (Shah et al, 2016 andBano and. This is may be due to role of citric acid in lowering the intestinal pH in the optimum conditions to the phytase, which led to Anthonius et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The result revealed that fish fed D5 had the highest a significant different (p < 0.05) on growth performance and feed utilization in comparison to the control and diets of interaction phytase and citric acid. This is in agreement with other studies on different species including L. rohita (Shah et al, 2016 andBano and. This is may be due to role of citric acid in lowering the intestinal pH in the optimum conditions to the phytase, which led to Anthonius et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…The group of fish fed on D4 had highest a significant difference (p<0.05) in growth performance and feed utilization in comparison to the control and phytase diets. This is in agreement with other studies on different species including tilapia (Maas et al, 2018 andAbo Norag et al, 2018), L. rohita (Shah et al, 2016 andBano and and Cirrhinus mrigala (Hussain et al, 2017). The increased growth response may be due to increased availability of nutrients and minerals by enzymatic breakdown of phytatenutrient complexes (Shah et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In recent years, the use of plant proteins in diets of aquatic organisms has increased in the aquaculture world (Bano & Afzal, 2017; Hossain et al, 2018; Yao, Li, Chowdhury, Wang, & Leng, 2019). However, the presence of antinutritional factors limits these ingredients being used in feed (Daranee & Dallen, 2011; Yao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Among the organic acids used in fish diet formulations, citric acid is notable for its positive results for zootechnical performance by enhancing dietary nutrient digestibility and general animal health (Bano & Afzal, 2017; Bour, Esmaeili, & Kenari, 2018; Lückstädt, 2008; Sarker et al, 2007; Sugiura, Dong, & Hardy, 1998; Zhu, Qiu, Ding, & Wang, 2014). Citric acid inclusion levels of 2 and 3% have improved the ash, calcium, and phosphorus contents of muscle and bones in juvenile beluga sturgeon, Huso huso , (Khajepour & Hosseini, 2012).…”
Section: Introductionmentioning
confidence: 99%